Evaluation of a co-facilitated information and learning programme for service users: the EOLAS programme. (7th June 2020) - Higgins, A.; Downes, C.; Monahan, M.; Hevey, D.; Boyd, F.; Cusack, N.; Gibbons, P.
Abstract : Background: The co-production and co-facilitation of recovery-focused education programmes is one way in which service users may be meaningfully involved as partners. Objectives: To evaluate the impact of a clinician and peer co-facilitated information programme on service users' knowledge, confidence, recovery attitudes, advocacy and hope, and to explore their experience of the programme. Methods: A sequential design was used involving a pre–post survey to assess changes in knowledge, confidence, advocacy, recovery attitudes and hope following programme participation. In addition, semi-structured interviews with programme participants were completed. Fifty-three participants completed both pre- and post-surveys and twelve individuals consented to interviews. Results: The results demonstrated statistically significant changes in service users' knowledge about mental health issues, confidence and advocacy. These improvements were reflected in the themes which emerged from the interviews with participants ( n = 12), who reported enhanced knowledge and awareness of distress and wellness, and a greater sense of hope. In addition, the peer influence helped to normalise experiences for participants, while the dual facilitation engendered equality of participation and increased the opportunity for meaningful collaboration between service users and practitioners. Conclusions: The evaluation highlights the potential strengths of a service user and clinician co-facilitated education programme that acknowledges and respects the difference between the knowledge gained through self-experience and the knowledge gained through formal learning.